2021
DOI: 10.1088/1742-6596/1810/1/012060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of problem-based learning on critical thinking skills

Abstract: Students’ critical thinking skills cannot develop appropriately if in the learning process, the teacher is not active. Therefore, to improve students’ critical thinking skills, a teacher should choose and use strategies, approaches, and methods techniques that involve students actively in learning, both in manner mental, physical, and social. One alternative learning that provides opportunities for students to develop students’ critical thinking skills in problem solving is problem-based learning. This researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
2
15
0
3
Order By: Relevance
“…Students' critical thinking skills claim a positive effect on solving problems. This makes students strive to solve a problem and develop critical thinking skills (Amin et al, 2020;Vossen et al, 2020). The results of this study were strengthened by stating that there was an increase in using the STEM learning model on 21st century skills development ( Han et al, 2015;Lavi et al, 2021;Sleeman et al, 2019).…”
Section: Discussionmentioning
confidence: 72%
“…Students' critical thinking skills claim a positive effect on solving problems. This makes students strive to solve a problem and develop critical thinking skills (Amin et al, 2020;Vossen et al, 2020). The results of this study were strengthened by stating that there was an increase in using the STEM learning model on 21st century skills development ( Han et al, 2015;Lavi et al, 2021;Sleeman et al, 2019).…”
Section: Discussionmentioning
confidence: 72%
“…The problem-based learning model is an innovative learning model that provides active learning conditions for students to construct the concepts they learn and develop their abilities by applying scientific methods in solving problems and developing critical thinking (Fadilla et al, 2021). Problem-based learning provides a major role for students to be able to investigate problems in finding solutions to a given problem, this means educators provide space for students to criticize the extent to which problems can be overcome and what solutions can be applied as a way to solve problems (Ramadhani et al, 2020;Nopia et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This learning model presents real problems in everyday life so that students can think logically in solving a problem. This is because the use of the PBL model focuses on the chosen problem so that students not only learn the concepts related to the problem but also the scientific method to solve the problem (Fadilla et al, 2021). The Problem Based Learning (PBL) model emphasizes the center of the problem, from instructional objectives to student behavior, methods and techniques to be used, to the measurement and evaluation process that will be carried out (Bayrak & Gürses, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…It is related to Saiful amin et, al research (2020) on title "Effect of problem-based learning on critical thinking skills and environmental attitude" it showed that there were significant influence Problem Based Learning on students' critical thinking and Environment attitude. The students tend to respond directly about learning process when they meet real world [27].…”
Section: Hypothesis Testmentioning
confidence: 99%